2019
DOI: 10.1055/a-1010-6052
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Reliability Criteria for Liver ElastPQ Shear Wave Elastography (ElastPQ-SWE): Comparison Between 10, 5 and 3 Measurements

Abstract: Purpose ElastPQ is a new elastography technique for non-invasive liver fibrosis staging. However, it does not have validated reliability criteria. We tested the reliability of a different number of measurements in patients with chronic liver disease and explored whether the application of quality criteria improves the diagnostic performance. Materials and Methods All patients underwent liver stiffness assessment (LSM) with ElastPQ and Fibroscan (F-TE). The mean, median, standard deviation (SD) and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…pSWE.-Ten measurements are still recommended; however, studies have shown that there is no loss in accuracy with five measurements when the quality criterion of IQR/M is fulfilled (25)(26)(27)(28). In the study by Fang et al (25), six measurements were recommended; however, when only the values obtained with a high reliability (IQR/M, ≤30%) were considered, there was no difference between five and six measurements.…”
Section: Number Of Measurementsmentioning
confidence: 99%
“…pSWE.-Ten measurements are still recommended; however, studies have shown that there is no loss in accuracy with five measurements when the quality criterion of IQR/M is fulfilled (25)(26)(27)(28). In the study by Fang et al (25), six measurements were recommended; however, when only the values obtained with a high reliability (IQR/M, ≤30%) were considered, there was no difference between five and six measurements.…”
Section: Number Of Measurementsmentioning
confidence: 99%
“…The most important criterion for a measurement of good quality seems an IQR/M ≤30% when the results are reported in Young's modulus [29]. This ratio, in fact, is a measure of the variability between consecutive acquisitions, and studies have reported a decrease in accuracy when this criterion is not fulfilled [37][38][39][40][41]. For measure-ment reported in m/s the IQR/M should be ≤15% because the conversion between the two is not linear [29].…”
Section: Description Of Quality Parametersmentioning
confidence: 99%
“…Based on literature data, for the pSWE technique the EFSUMB and WFUMB guidelines have recommended to use the median value of 10 acquisitions [3,4,9]. However, some studies have shown that the accuracy does not decrease when fewer acquisitions (up to five) are obtained [38][39][40]42]. For 2D-SWE, the EFSUMB updated guidelines have recommended to obtain at least three acquisitions [3,4].…”
Section: How Many Measurements?mentioning
confidence: 99%
“…Moreover, our study assessed the performance of the p-SWE technique with fewer measurements. In agreement with other recent evidence evaluating cohorts with different etiologies of chronic liver disease, we observed that SWE-5 provided the highest diagnostic performance (AUROC), sensitivity, and specificity for both significant (0.809, 77.8%, and 73.4%, respectively) and advanced fibrosis (0.809, 77.8%, and 75.0%, respectively) with respect to SWE-10 and for significant fibrosis with respect to TE, even if the differences were not statistically significant [22,23]. Interestingly, when exploring alternative cutoffs for maximizing sensitivity and specificity, SWE-5 with a cutoff of ≥7.6 kPa yielded an increase in sensitivity to 94.4%, with only a slight drop in specificity (60.7%) for the diagnosis of advanced fibrosis.…”
Section: A)mentioning
confidence: 78%